Gut Microbiota Modulation by Selenium and Zinc Enrichment Postbiotic on Dysbiosis Associated with Hypertension - Dinu, Laura-Dorina; Gatea, Florentina; Matei, Florentina; Banciu, Cristian; Vamanu, Emanuel (Current Vascular Pharmacology, 2024)
Background: Targeting gut dysbiosis to treat chronic diseases or to alleviate the symptoms is a new direction for medical adjuvant therapies. Recently, postbiotics have received considerable attention as they are non-viable probiotic preparations that confer various health benefits to the host without the safety problems associated with using live microbial cells. Objective: The aim of the study is to obtain selenium (Se) and zinc (Zn) enriched Saccharomyces boulardii postbiotic biomass and to analyze its modulation effect because these minerals play an important role in reducing gut dysbiosis linked to cardiovascular (CV) diseases. Method: The effect of the S. boulardii and Se/Zn enriched yeast postbiotics on CV microbial fingerprint was studied in vitro using the gastrointestinal system (GIS 1) and analyzed by microbiological, chemical, and qPCR methods. Result: There was a 2.2 log CFU/mL increase in the total bacterial load after SeZn postbiotic treatment and in the qPCR counts of Firmicutes phyla for both treatments. Beneficial taxa, Bifidobacterium spp. and Lactobacillus spp., as well as Bacteroidesspp. were up to 1.5 log higher after mineral- enriched postbiotic application, while the acetic acid level increased. Conclusion: These preliminary studies highlight the therapeutic potential of using Se/Zn enriched yeast postbiotics as adjuvants for clinical treatments of CV diseases
Keywords: hypertension associated dysbiosis